Psychosocial and Culturally-Specific Factors Related to Intimate Partner Violence Victimization among a Sample of Latino Sexual Minority Cis Men in the U.S. Issue 23 (December 2022) - Robles, Gabriel; Bosco, Stephen C.; Cardenas, Iris; Hostetter, Joletta; Starks, Tyrel J.
A growing body of research illustrates that sexual minority men (SMM) experience elevated rates of intimate partner violence (IPV) compared to heterosexual individuals. Researchers have examined the relationship between minority stress and IPV victimization among sexual minority men. A majority of the IPV research identifying risk factors associated with IPV victimization among SMM have sampled predominately non-Hispanic White SMM, while Latino SMM are consistently under-represented in IPV research. This study examines the associations between (1) co-occurring psychosocial factors (e.g., depression, anxiety, childhood sexual abuse, drug use, and problematic drinking) and (2) Latino-specific minority stress factors (e.g., U.S.-born, language, race/ethnic identities, and discrimination) on IPV victimization in a nationwide sample of Latino SMM. Data were collected from Latino SMM aged 18 or older, identified as cis-male, and in a romantic relationship with a cis-male partner ( N = 530). The participants were recruited through social media and geo-location-based dating mobile applications. A majority (72%) of the sample reported IPV victimization in their lifetime. Specific to forms of IPV, more than half (51.9%) of the sample reported monitoring behaviors, while 49.6% reported emotional IPV, 45.1% reported physical IPV, 31.5% reported controlling behaviors, and 22.3% reported HIV-related IPV. In multivariable models, psychosocial and Latino-specific factors were associated with the increased likelihood of IPV victimization. Regarding Latino-specific factors, being born in the U.S. and race-based discrimination predicted IPV victimization. These findings highlight the extent to which minority stress elevates the risk of IPV for Latino SMM and point to the need to address social factors in IPV prevention services. Further, work on SMM IPV victimization tends to focus on the potential role of sexual orientation-related discrimination, whereas the current study points to the importance of race-based discrimination.